1996
DOI: 10.1002/(sici)1097-4628(19961121)62:8<1263::aid-app17>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

A hot‐melt pressure‐sensitive adhesive based on styrene‐butadiene‐styrene rubber. The effect of adhesive composition on the properties

Abstract: SYNOPSISHot-melt pressure-sensitive adhesives based on styrene-butadiene block copolymers with aliphatic and aromatic tackifying resins and plastifying oils have been analyzed. The importance of the resin structure in the compatibility with the block copolymer and the influence of the different paraffinic-naphthenic character of the oil in PSA performance have been shown. Ternary systems with a fixed polymer content (30%) and with variable resin and oil contents show a good miscibility over the whole range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…SIS consists of two incompatible blocks in the solid state, the isoprene segments with lower T g and the styrene segments with upper T g , which form a microphase‐separated structure at room temperature 17–19. The material can be considered as an elastermeric matrix physically vulcanized by the aggregation of polystyrene (PS) end blocks, which also act as reinforcing filler 20–22.…”
Section: Introductionmentioning
confidence: 99%
“…SIS consists of two incompatible blocks in the solid state, the isoprene segments with lower T g and the styrene segments with upper T g , which form a microphase‐separated structure at room temperature 17–19. The material can be considered as an elastermeric matrix physically vulcanized by the aggregation of polystyrene (PS) end blocks, which also act as reinforcing filler 20–22.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been found that two‐phase systems generally violate the time‐temperature superposition, the master curves of loss tangent delta are also shown in Figure for validation. The level of compatibility between the tackifiers and the biopolymer can also be evaluated from Figure as Galan et al . have shown in their work on HMPSAs based on SBS rubber.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been found that two-phase systems generally violate the time-temperature superposition, the master curves of loss tangent delta are also shown in Figure 7 for validation. The level of compatibility between the tackifiers and the biopolymer can also be evaluated from Figure 7 as Galan et al 28 have shown in their work on HMPSAs based on SBS rubber. Generally, more intense peaks correspond to higher levels of compatibility between the components, and from Figure 7 it can be concluded that at low and intermediate frequencies tackifiers 3 and 5 have better compatibility with the biopolymer rather than tackifier 4 as they display more intense peaks.…”
Section: Rheology Measurementsmentioning
confidence: 99%
“…For this reason, techniques for the sequential application of both methods would enable the construction of a much broader palette of heterogeneous copolymers. Styrene/diene based block copolymers, which are used extensively in various industries such as paving and construction, adhesives, and paints and coatings, could be supplanted with styrene/butyl acrylate analogs. A natural strategy for the marriage of RAFT and anionic polymerization is the construction of CTA functionality from the terminus of a living polyanion.…”
Section: Introductionmentioning
confidence: 99%